2021
DOI: 10.3390/ijms22052578
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Pathogen Dose and PI3Kγ in Immunometabolic Reprogramming of Microglia for Innate Immune Memory

Abstract: Microglia, the innate immune cells of the CNS, exhibit long-term response changes indicative of innate immune memory (IIM). Our previous studies revealed IIM patterns of microglia with opposing immune phenotypes: trained immunity after a low dose and immune tolerance after a high dose challenge with pathogen-associated molecular patterns (PAMP). Compelling evidence shows that innate immune cells adopt features of IIM via immunometabolic control. However, immunometabolic reprogramming involved in the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Initial studies disclosed the stressor-dependent induction of both trained immunity and tolerance in monocytes and macrophages, where priming by β-glucan or BCG triggers training, distinct from LPS-priming that results in tolerance upon a second infection insult [3,4,13,14]. Subsequently, dose-dependent priming effects mediating both memory-like responses in innate immune cells were established [5,15,[49][50][51]. Moreover, studies from our group also revealed the magnitude of priming and the cellular maturation state as important factors in the development of memory-like patterns [7].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies disclosed the stressor-dependent induction of both trained immunity and tolerance in monocytes and macrophages, where priming by β-glucan or BCG triggers training, distinct from LPS-priming that results in tolerance upon a second infection insult [3,4,13,14]. Subsequently, dose-dependent priming effects mediating both memory-like responses in innate immune cells were established [5,15,[49][50][51]. Moreover, studies from our group also revealed the magnitude of priming and the cellular maturation state as important factors in the development of memory-like patterns [7].…”
Section: Discussionmentioning
confidence: 99%
“…PI3Kγ was identified as the major PI3K catalytic isoform in primary myeloid cells, as these cells express at least 25-fold more PI3K than other isoforms [27]. We and others showed solid expression of PI3Kγ in primary microglial cells [9,28] and documented their crucial impact on the microglial immune response: directed migration, MMP-9 expression and phagocytic activity following systemic inflammation and focal brain ischemia/recirculation as well as modulation of innate immune memory [10,24,26,[29][30][31].…”
Section: Introductionmentioning
confidence: 69%
“…Based on the previous evidence of PI3Kγ-dependent control of different microglial cell functions including phagocytosis [9], microglial motility [10], memory-like inflammatory responses [29] and immunometabolic reprogramming for innate immune memory [30], a certain influence of PI3Kγ on microglial proliferation was anticipated. However, whereas PI3Kγ-dependent modulation of microglial phagocytic activity was clearly mediated by lipid kinase-independent stimulation of phosphodiesterase activity, leading to reduced intracellular cAMP with suppressed phagocytic activity [9], PI3Kγ lipid kinase activity was identified as an essential mediator of microglial migration and memory-like effects in microglia [10,29,30]. The present data verify that the lipid kinase activity of PI3Kγ is responsible for microglial proliferative activation and improved cell viability due to inflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Each compound was injected consecutively. The OCR and ECAR were measured in picomoles per minute and milli-pH units per minute, respectively, in cycles of 3 min mix and 3 min measure periods at 37 • C. At the end of the measurement, cell densities per well were quantified by crystal violet staining as previously described [25] and the observed OCR and ECAR were normalized to the corresponding cell densities. Wave Desktop 2.6 software (Agilent Technologies, Waldbronn, Germany) was used to analyze the datasets.…”
Section: Seahorse Analysis Of Cellsmentioning
confidence: 99%